(untitled) (Práxis Educativa, 2024)
Analysing methods for integrating modern interactive techniques into university curricula is necessary due to the growing digitalization of education. The research seeks to assess the effectiveness of current interactive teaching methods, explore their potential integration with traditional approaches, and examine their influence on student learning outcomes. The study employs analytical, systematic, statistical, comparative, synthesis, and deduction methods to demonstrate that interactive methods can be categorised and evaluated in relation to other pedagogical techniques. The integration of interactive and conventional methods has been demonstrated to improve student achievement. The paper emphasises the necessity of incorporating interactive methodologies in addition to lectures for English-taught inorganic chemistry courses. A survey of 16 university instructors indicates that the most frequently employed interactive approaches are situational methods (88%), discussion methods (63%), and experimental methods (75%), often used in combination. Interactive learning is defined in the paper as the process of promoting two-way communication between instructors and students in order to enhance engagement and expedite the acquisition of knowledge. The use of the English language provides benefits such as the ability to access primary scientific literature and the development of skills necessary for international professional opportunities. The obtained results have practical significance as they can be utilised to create methodological materials and provide recommendations for teachers in higher educational institutions, colleges, or specialised schools that teach inorganic chemistry in English. Keywords: Digitalization. Educational process. Pedagogical approaches. Exact sciences. Higher education seekers.